METODE KOMBINASI DALAM MENAFSIRKAN SURAT AL-AHZAB (33) : 33 - Maulana Maulana (CV. Adiba Aisha Amira, 2021)
This paper describes the method of interpreting the Koran, the author considers that the interpretation of the Koran is carried out with various methods and ways that have been determined in the rules of interpretation, both through approaches, history, linguistics, social, science, and looking at the interpretations of the commentators. interpretation into four kinds. First, this Tahli>li method seeks to explain the content of the verses of the Qur'an from various aspects, according to the views, tendencies, and wishes of the commentators which are presented in a coherent manner in accordance with the order of the verses in the manuscripts. Second, this ijma>li or global method describes the general meanings contained by the verse. Third, muqa>ran or comparison. The interpretation model in this method is to present verses of the Koran with different editorials from one another, to present verses that have different information content from the hadith and to present various interpretations of the scholars. Fourth, maudhu>'i or thematic, namely methods that direct view on a particular theme. Then look for a particular theme by collecting all the verses that talk about it, analyzing and understanding verse by verse to get a complete interpretation of the theme being discussed.